The challenges in using electronic documentation management system among workers in George Kent (M) Sdn. Bhd. / Nur Amalina Nasaruddin - Nasaruddin, Nur Amalina (Faculty of Business and Management, 2018)
The purpose of this study is to explore the challenges in using electronic documentation management system among workers in George Kent (M) Sdn Berhad. The researcher wants to find out what are the challenges in using electronic documentation management system among workers in Geoge Kent (M) Berhad. This study is using a qualitative methodology. Data was collected through interview with the respondents. Four interview were conducted by the researcher. The respondents are the employees of George Kent (M) Sdn Berhad. Purposive sampling is used in this study. This is because the respondents are the one that are experience in organization. This study concludes that organizations need to realize the importance to implement electronic documentation system in ways to enhance efficiency and reduce errors in their process.